2020
DOI: 10.3390/ijms21217950
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Direct Cardiac Reprogramming: Any GMT Cocktail Variety?

Abstract: Direct cardiac reprogramming has emerged as a novel therapeutic approach to treat and regenerate injured hearts through the direct conversion of fibroblasts into cardiac cells. Most studies have focused on the reprogramming of fibroblasts into induced cardiomyocytes (iCMs). The first study in which this technology was described, showed that at least a combination of three transcription factors, GATA4, MEF2C and TBX5 (GMT cocktail), was required for the reprogramming into iCMs in vitro using mouse cells. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…Although significant progress has been made in the cardiac reprogramming field in recent years, robust and reproducible protocols are still needed to be set up in vitro, mainly in the case of human cells, before this strategy can be translated into the clinic. (López-Muneta et al, 2020;Garry et al, 2021). In this study, we have generated functional human NKX2.5 GFP cFib to facilitate screening factor research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although significant progress has been made in the cardiac reprogramming field in recent years, robust and reproducible protocols are still needed to be set up in vitro, mainly in the case of human cells, before this strategy can be translated into the clinic. (López-Muneta et al, 2020;Garry et al, 2021). In this study, we have generated functional human NKX2.5 GFP cFib to facilitate screening factor research.…”
Section: Discussionmentioning
confidence: 99%
“…This is important to take into consideration since direct cardiac reprogramming in vivo is considered a more feasible therapeutic approach than in vitro, as it has shown a higher reprogramming efficiency (Qian et al, 2012;Song et al, 2012) and can circumvent one of the major problems of cell therapy, namely poor engraftment. (López-Muneta et al, 2020). Alternatively, enhancement of reprogramming efficiency to obtain human iCM would be critical to produce sufficient cells in vitro for transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of multipotent iCPCs may offer additional benefits for heart regeneration as they have the potential to differentiate into endothelial and smooth muscle cells, thereby promoting vasculogenesis. Further, while iCMs rapidly exit the cell cycle upon reprogramming, iCPCs remain proliferative until they differentiate into CMs (reviewed in Klose et al, 2019 ; Lopez-Muneta et al, 2020 ). Overexpression of OCT4, KLF4, SOX2, and C-MYC in MEFs, which is well-known to generate iPSCs (Takahashi and Yamanaka, 2006 ; Takahashi et al, 2007 ), was observed to generate small clusters of contracting colonies by day 18 in the absence of leukemia inhibitor factor (LIF) (Efe et al, 2011 ).…”
Section: Strategies For Cardiac Repairmentioning
confidence: 99%
“…Nonetheless, in vivo studies performed in mice have highlighted a number of challenges that remain to be overcome before this approach could be used in the human clinic, like the low efficiency of conversion, the immaturity, at least in vitro, of reprogrammed cells, the absence of safe delivery methods, and the inability to precisely direct differentiation towards the desired cell subtype [7,16]. Generation of multipotent iCPCs instead of iCMs may offer some advantages for heart regeneration as they have the potential to differentiate into different cardiac cell lineages, retaining a certain ability to proliferate [99].…”
Section: Direct Cardiac Reprogramming Of Cardiac Fibroblasts Into Cardiomyocytesmentioning
confidence: 99%